Bifunctionality from Synergy: CoP Nanoparticles Embedded in Amorphous CoOx Nanoplates with Heterostructures for Highly Efficient Water Electrolysis - Yu, J.; Zhong, Y.; Wu, X.; Sunarso, J.; Ni, M.; Zhou, W.; Shao, Zongping (WILEY-BLACKWELL, 2018)
© 2018 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Hydrogen production from renewable electricity relies upon the development of an efficient alkaline water electrolysis device and, ultimately, upon the availability of low cost and stable electrocatalysts that can promote oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Normally, different electrocatalysts are applied for HER and OER because of their different reaction intermediates and mechanisms. Here, the synthesis of a heterostructured CoP@a-CoOx plate, which constitutes the embedded crystalline cobalt phosphide (CoP) nanoclusters and amorphous cobalt oxides (CoOx) nanoplates matrix, via a combined solvothermal and low temperature phosphidation route is reported. Due to the presence of synergistic effect between CoP nanoclusters and amorphous CoOx nanoplates in the catalyst, created from the strong nanointerfaces electronic interactions between CoP and CoOx phases in its heterostructure, this composite displays very high OER activity in addition to favorable HER activity that is comparable to the performance of the IrO2OER benchmark and approached that of the Pt/C HER benchmark. More importantly, an efficient and stable alkaline water electrolysis operation is achieved using CoP@a-CoOx plate as both cathode and anode as evidenced by the obtainment of a relatively low potential of 1.660 V at a 10 mA cm-2current density and its marginal increase above 1.660 V over 30 h continuous operation.